Corte costituzionale e "materia penale" I confini mobili delle garanzie penalistiche, tra Costituzione e Carte internazionali - BISSARO, STEFANO (Politica, diritto, 2022)
The progressive affirmation of the European criminal law and the increasingly activity of the European Courts in criminal field have profoundly affected the corollaries of the principle of criminal legality, enshrined in Article 25, second paragraph, of the Italian Constitution. On the domestic side, too, the evolution of this principle has distanced the guarantees of nullum crimen from the design that the Constituent had outlined, in homage to their Enlightenment genesis. In this context, doctrine and jurisprudence, both national and supranational, have dealt in particular with the dilemma of "criminal matter", that means with the problem of the boundaries of the principle of legality referred to in Article 25, second paragraph, Const.; this topic has taken on a very special relevance in recent times, after the Constitutional Court elevated nullum crimen to the rank of supreme principle of our legal system, insofar as it imposes determinacy and non-retroactivity in malam partem. The present volume aims to investigate these issues, from the peculiar perspective of constitutional law, trying to measure the advantages and costs, also from a systematic point of view, of an elastic notion of "criminal matters".